Structural Feasibility Assessment of an Adjustable-Height Photovoltaic Mounting System Using Conceptual Design and Finite Element Simulation - Faizin, Muhammad Ihsan Nur; Yandri, Erkata (Heca Journal of Applied Sciences, 2026)
The performance of photovoltaic (PV) systems is influenced not only by module efficiency but also by the flexibility and structural reliability of mounting systems, particularly those allowing height and tilt adjustments to accommodate site-specific and seasonal variations. While automatic tracking systems can increase energy yield, their high cost and mechanical complexity limit widespread adoption, underscoring the need for simpler, more economical alternatives. This study evaluates the structural feasibility of an adjustable-height PV mounting system that improves installation flexibility while maintaining mechanical integrity. A conceptual engineering design approach was employed to develop a modular mounting structure with a mechanical height-adjustment mechanism. Structural performance was assessed using finite element–based static simulations under gravitational loading representative of a commercial bifacial PV module. The evaluation focused on Von Mises stress distribution, total deformation, and safety factor as indicators of mechanical reliability at the conceptual design stage. The results indicate that maximum Von Mises stress remains well below the assumed material yield strength, while total deformation is negligible relative to overall structural dimensions. The calculated safety factor confirms an adequate structural safety margin, indicating that integrating a height adjustment mechanism does not compromise structural stability. The proposed mounting system demonstrates sufficient structural feasibility and mechanical simplicity for early-stage development, offering a practical, adaptable solution for ground-mounted and rooftop PV installations.